A machine learning-based framework for Predicting Treatment Failure in tuberculosis: A case study of six countries. (July 2020) - Asad, Muhammad; Mahmood, Azhar; Usman, Muhammad
Abstract: Tuberculosis is ranked as the 2nd deadliest disease in the world and is responsible for ten million deaths in 2017. Treatment failure is one of a main reason behind these deaths. Reasons of treatment failure are still unknown and the death rate due to TB is increasing. Machine learning and data analytics approaches are proved to be useful in healthcare domain in finding the associations among different attributes that can affect the outcome of any disease. Timely identification of reasons can save a patient's life. This study aims to find features that are strongly correlated with treatment failure using feature selection techniques. The validation of features is demonstrated using different classification algorithms. Moreover, this study provides a demographic based feature association of six highly burdened treatment failure countries. A verified real-life patient's dataset gathered from different countries including Azerbaijan, Belarus, Georgia, India, Moldova, and Romania is utilized to address the problem. Two types of experimentation are performed on combined dataset by achieving an average accuracy of 78% and an accuracy of 92% on Romania's data. Results shows the importance of features obtained through this study are highly influential in leading a patient towards treatment failure.